HLA-DR expression in cytotoxic T lymphocytes: a key to boost the therapeutic potential of T cell-based strategies for breast cancer - Salvador, Rute; Correia, Bruna Filipa; Grosa, Daniela; Martins, Telma; Soares Baal, Suelen Cristina; Saraiva, Diana Pereira; Cristóvão-Ferreira, Sofia; Pereira, Isabel Lopes; Rebelo de Almeida, Cátia; Fior, Rita; Jacinto, Antonio; Mathias, Carolina; et al. (Frontiers in Immunology, 2025)
T cell-based therapies, involving ex vivo expansion of patients’ T lymphocytes, hold significant promise for chemotherapy resistant cases of breast cancer (BC), although their effectiveness remains challenging. Building on our previous findings that the expression of the antigen presenting molecule, HLA-DR, is crucial on tumor-infiltrating cytotoxic T lymphocytes (CTLs) for a favorable response to neoadjuvant chemotherapy, we further investigated the role of HLA-DR-expressing CTLs in anti-tumor responses and evaluated strategies to amplify these cells. Through in vitro and in vivo experiments, we demonstrated that HLA-DR expression on CTLs is important for effective tumor cell elimination. Notably, blocking HLA-DR or depleting CD4+ T cells impaired CTLs activation, suggesting a critical role for antigen presentation by CTLs to CD4+ T cells through HLA-DR in promoting robust anti-tumor responses. Based on these findings we optimized an ex vivo stimulation protocol that increases the proportion of HLA-DR+CTLs with improved cytotoxicity, prioritizing cell quality over yield. Moreover, we showed that adding anti-PD-1 to the stimulation, further upregulated HLA-DR expression, and intensified CTLs’ cytotoxic ability. This aligns with our in silico analysis suggesting a potential regulatory link between PD-1 and HLA-DR via non-coding RNAs. Overall, our findings open new avenues for advancing T cell-based therapies and improve the outcomes of chemotherapy-resistant-BC.